In vivo characteristics of human immunodeficiency virus type 1 intersubtype recombination: Determination of hot spots and correlation with sequence similarity - Magiorkinis, G; Paraskevis, D; Vandamme, A; Magiokinis, E; Sypsa, V; Hatzakis, A (2003)
Recombination plays a pivotal role in the evolutionary process of many different virus species, including retroviruses. Analysis of all human immunodeficiency virus type 1 (HIV-1) intersubtype recombinants revealed that they are more complex than described initially. Recombination frequency is higher within certain genomic regions, such as partial reverse transcriptase (RT), vif/vpr, the first exons of tat/rev, vpu and gp41. A direct correlation was observed between recombination frequency and sequence similarity across the HIV-1 genome, indicating that sufficient sequence similarity is required upstream of the recombination breakpoint. This finding suggests that recombination in vivo may occur preferentially during reverse transcription through the strand displacement-assimilation model rather than the copy-choice model.